Pelatihan Pelafalan (Pronunciation) Kosa Kata Bahasa Inggris Dengan Metode Drilling Bagi Siswa Sekolah Dasar - Suprih Ambawani; Bernadetta Eko Putranti (CV. Multi Kreasi Media, 2023)
The purpose of this community service program is to give positive activities to children in Jetisharjo, RT 25/RW 06, Cokrodiningratan, Yogyakarta by teaching them to pronounce English words through the drilling method. The method used in this community service program is a demonstration. This activity is carried out by teaching the children to pronounce English words, phrases, or sentences repeatedly until they can pronounce them correctly. The results of this community service activity show that children's ability to pronounce English vocabulary has increased rapidly using the drilling method. Furthermore, through this community service program, they have more confidence in pronouncing English words and sentences.